A manutenção no (extra) ordinário trabalho de uma borracharia: a construção do aprendizado do trabalhador entre a produção, a segurança e a saúde - Daniel de Souza Costa (2009)
This research approaches the worker inserted in its work context which is characterized by a dialog and conflict between these two realities: the prescription established on rules, standards, proceedings and on other forms of anticipation of the work and the worker activity, noticed in the acting, interpretation and intervention of the worker to supply and materialize the demands proposed by of the capital. In this coming and going, finding and loosing created by the relationship between capital and work, the subject themselves, the workers; start to live and to work constantly the standards and values that are valid for the society. The investigation carried out in a workshop of equipments of mining from the Company Vale do Rio Doce, specifically in a tire repair shop, in a city called Nova Lima in Minas Gerais state, between the years 2007 and 2009, tried to understand the real work situation, revealing how they built their knowledge and the reasons that were taking them to be exposed to the risks of accidents to reach the production objectives. This understanding of the reality of the workers can, produce ,at least partially, interventions and transformations on the conditions of work that can maintain and built the health of workers.